Hypostases of the mask motif in the Greek poetry from the beginning of the 20th century (Colloquia Comparativa Litterarum, 2025)
The article examines the work and biographies of Romos Filiras and Napoleon Lapathiotis, representatives of the generation of poets from the first decades of the 20th century, considered to be the forerunners of Greek 1920s poetic cosmopolitanism. It also presents an analysis of the ‘hypostases’ of the mask motive in their work. Opinions of literary critics from different university schools regarding the considered authors are compared. References:Balourdos, G. (1995). Napoleon Lapathiotis – o chronos kai o thanatos. Odos Panos, (79–80), [p. [Not specified]].Bozonis, A. (n.d.). Enas kataramenos tis ellinikis poiisis. http://www.elculture.grChaplin, Ch. (1966). My autobiography. Pocket books.Chartokollis, P. (2003). Idanikoi aftocheires. Ellines logotechnes pou aftoktonisan. Vivliopoleion tis Estias.Dimouli, A. (n.d.). Idyoneiro kai pragmatikotita i o poiitis Romos Filyras kai o «pierotos»: scheseis taftotitas kai ekfanseis tou poiitikou ypokeimenou. https://www.vakxikon.grFilyras, R. (1981). Portraita kai keimilia – anekdota poiimata. Kissos.Filyras, R. (2013). Poiimata – apanta ta evrethenta. University Studio Press.Filyras, R. (2021, May 17). O pierotos. https://www.timesnews.gr/romos-filyras-o-pierotos/Ifanidis, Ya. (2002). Edip. In Koi sa gartsite (savremenna gratska eseistika) (p. [Not specified]). Kolektsia akvarium – Sredizmnomorie.Karyotakis, K. (1972). Poiimata kai peza (G. P. Savvidis, Ed.). Ermis.Kerrigan, M. (2015). Gustav Klimt, art nouveau, and the Vienna secessionists. Flame Tree Publishing.Politis, L. (1980). Istoria tis neoellinikis logotechnias. MIET.Sarantakos, N. (n.d.). [No title specified]. https://www.sarantakos.com/liter/lapathiotis/erwtiko.htmlSavremenna gratska poezia (Vol. 2) (St. Gechev, Trans.). (1997). Epsilon.Storey, R. F. (2014). A critical history of a mask. Princeton University Press.Trypanis, K. (1988). Elliniki poiisi. Estia.Voutouris, P. (2000). Logotechnikes anazitiseis. In Istoria tis Ellados tou 20ou aiona (p. [Not specified]). Vivliorama.
Keywords: Greek poetry; Greek literary critics; Romos Filiras; Napoleon Lapathiotis; mask motif